Urban resident perceptions of the impacts of tourism development in Zimbabwe - Tichaawa, Tembi M.; Moyo, Sakhile (Bulletin of Geography. Socio-economic Series, 2019)
This study examines the perceptions of urban residents towards the socio-economic and environmental consequences of tourism development in Zimbabwe. Perceptions were tested using empirical data that were gathered from a sample of 384 adult members, representing urban households in Bulawayo. The results from a semi-structured survey revealed that such sociodemographic variables as gender, education, length of stay and income are relatively predictable of their attitude towards tourism. Further, although the urban residents tended to perceive tourism impacts positively, they reacted more strongly to the environmental impacts involved than to the economic and sociocultural impacts. The urban geographic context of this study makes this finding significant, as it indicates that urban residents have an environmental consciousness with regard to tourism. The study has implications for tourism development planners and destination managers, in terms of enhanced engagement with the urban residents regarding tourism development, irrespective of the likelihood of residents supporting future development.